Single Event Effects mitigation with TMRG tool. (26th January 2017) - Kulis, S.
Abstract: Single Event Effects (SEE) are a major concern for integrated circuits exposed to radiation. There have been several techniques proposed to protect circuits against radiation-induced upsets. Among the others, the Triple Modular Redundancy (TMR) technique is one of the most popular. The purpose of the Triple Modular Redundancy Generator (TMRG) tool is to automatize the process of triplicating digital circuits freeing the designer from introducing the TMR code manually at the implementation stage. It helps to ensure that triplicated logic is maintained through the design process. Finally, the tool streamlines the process of introducing SEE in gate level simulations for final verification.